Junk Drawer - Lisa Phan (Stimulus: A Medical Humanities Journal, 2023)
Children can be confused a lot of the times and children can definitely be confused in a healthcare setting. When you expect a child to confidently and accurately interpret a family member's checkup or test result, there is a lot of space for miscommunication. It's like pulling from a junk drawer; not enough and not relevant enough to help in the situation given the limited knowledge and vocabulary. But as the only immediate person able to fill the gap between two languages, bilingual children are often forced to open this junk drawer and desperately hope a hiccup in their understanding doesn't result in something detrimental for their sick family member.